Fatostatin delayed lip sensory recovery after inferior alveolar nerve transection by inhibiting sterol regulatory element-binding protein 1 - Suning Mao; Zhongkai Ma; Gaowei Zhang; Pingchuan Ma; Chunjie Li; Li Ye (Journal of Dental Sciences, 2025)
Lipid metabolism is essential for nerve repair in damaged nerves. Fatostatin, a selective inhibitor of sterol regulatory element-binding protein 1 (SREBP1), could reduce cholesterol synthesis and disturb lipid homeostasis. However, whether fatostatin would delay lip sensory recovery after inferior alveolar nerve transection remains unclear. In this preliminary study, we investigated the effects of fatostatin on lip sensory recovery in vivo and axon growth in vitro. Fatostatin significantly delayed lip sensory recovery of mice after inferior alveolar nerve transection as evidenced by quantitative sensory testing. Fatostatin also reduced the average axon length of primary trigeminal neurons. Despite SREBP1, expressions of other lipid metabolism-related (including fatty acid synthase and ATP citrate lyase) and axon regeneration-related molecules (including activating transcription factor 3 and nerve growth factor) were also inhibited, as evidenced by the Western Blot and quantitative real-time PCR. Overall, fatostatin delayed lip sensory recovery after inferior alveolar nerve transection by inhibiting SREBP1.